STRATEGIES FOR TRANSFORMING 21ST CENTURY EDUCATION TO REALISE COMPETITIVE HUMAN RESOURCES TOWARDS THE GOLDEN GENERATION: A LITERATURE REVIEW - Saepurokhman, Asep; R Pugu, Melyana; Meisarah, Fitria (Berajah Journal, 2025)
This research aims to examine 21st century education transformation strategies in an effort to realise competitive human resources (HR) towards Indonesia's golden generation. Through a literature review, this research highlights the importance of changing the educational paradigm, developing a competency and character-based curriculum, and utilising technology in the learning process. The transformation of 21st century education emphasises the mastery of critical thinking, creativity, communication and collaboration (4C) skills, as well as digital literacy as the main capital to face global challenges. Challenges identified include access gaps, limited infrastructure, resistance to change and the need to strengthen teacher capacity. Proposed solutions include strengthening teacher training, updating the curriculum, equalising access to technology and cross-sector collaboration. The results of the study show that an integrated and adaptive strategy is needed to produce human resources that are superior, innovative and characterised, so that they are ready to compete in the global era and contribute to realising the Golden Indonesia 2045.